EVALUASI DAN PENENTUAN PRIORITAS PERBAIKAN KUALITAS PELAYANAN FAKULTAS (STUDI KASUS FAKULTAS TEKNIK UNIVERSITAS ESA UNGGUL) (Universitas Esa Unggul, 2017)
AbstractThe expected long-term goal of this research is to improve the service quality of Faculty of Engineering Esa Unggul University. While the specific targets to be achieved in this study is to get a picture of expectation from the students about the service of Faculty of Engineering Esa Unggul University, futhermore, to get get a description of the perception of students' about service performance of Faculty of Engineering Esa Unggul University, each attribute and determine the priority of each attribute in accordance with the Importance Performance Analysis (IPA) matrix. The design of this research using quantitative non-experiment method, and also form of descriptive analysis. Data collection method is survey using questionnaire to obtain the type of data in the form of primary perception and expectations of respondents ie students of the Faculty of Engineering Esa Unggul University in the Academic Year 2017/2018. Method of data analysis using descriptive analysis to see the level of expectation and satisfaction/ performance/perception about service of Faculty of Engineering Esa Unggul University based on five dimension SERVQUAL. Furthermore, mathematical methods with quadrants are used to map and see attributes that become improvement priorities for services quality at Faculty of Engineering Esa Unggul University based on Importance Performance Analysis (IPA) matrix. This research is expected to be useful as a reference material to make changes in an effort to make continuous improvement based on priority to satisfy customers, especially for things that are considered important by the customer. The outcome of this research is the publication of scientific articles in unaccredited national journals.From the results of this study indicates that the attribute that becomes the first priority for improvement based on expectation value is the Reliability 4 attribute, and the dimension which is the most important factor in service is the Reliability Dimension. If based on the value of perception value, the attribute of first priority is the Tangible 1 attribute, and the dimension with the lowest performance is the Tangibles Dimension. For attribute of first priority for improvement based on satisfaction score (SERVQUAL score) is Reliability 4 attribute. From mapping result with IPA matrix based on attribute, there are 12 attributes that become main priority, that is: Tangible 1, Tangible 4, Reliability 1, Reliability 2, Reliability 3, Reliability 4, Responsiveness 2, Assurance 4, Assurance 5, Emphaty 2, Emphaty 3, Emphaty 4. While from the IPA matrix mapping result based on dimension, the main priority of improvement for Faculty of Engineering Esa Unggul University service is Reliability Dimension that is reliability in fulfilling promise to students. Keywords : SERVQUAL, importance-performance analysis, customer satisfaction AbstrakTujuan jangka panjang yang diharapkan dari penelitian ini adalah untuk meningkatkan kualitas pelayanan Fakultas Teknik Universitas Esa Unggul. Sedangkan target spesifik yang ingin dicapai dalam penelitian ini adalah untuk mendapatkan gambaran harapan dari mahasiswa tentang pelayanan Fakultas Teknik Universitas Esa Unggul, terlebih lagi, untuk mendapatkan gambaran tentang persepsi siswa tentang kinerja pelayanan Fakultas Universitas Teknik Esa Unggul, masing-masing atribut dan menentukan prioritas masing-masing atribut sesuai dengan matriks Importance Performance Analysis (IPA). Perancangan penelitian ini menggunakan metode non eksperimen kuantitatif, dan juga bentuk analisis deskriptif. Metode pengumpulan data adalah survei dengan menggunakan kuesioner untuk mendapatkan jenis data berupa persepsi primer dan harapan responden yaitu mahasiswa Fakultas Teknik Universitas Esa Unggul pada Tahun Akademik 2017/2018. Metode analisis data menggunakan analisis deskriptif untuk melihat tingkat harapan dan kepuasan/kinerja/persepsi tentang pelayanan akademik Fakultas Teknik Universitas Esa Unggul berdasarkan lima dimensi SERVQUAL. Selanjutnya, metode matematis dengan kuadran digunakan untuk memetakan dan melihat atribut yang menjadi prioritas peningkatan kualitas layanan di Fakultas Teknik Universitas Esa Unggul berdasarkan matriks IPA. Penelitian ini diharapkan dapat bermanfaat sebagai bahan referensi untuk melakukan perubahan dalam upaya melakukan perbaikan terus menerus berdasarkan prioritas untuk memuaskan pelanggan, terutama untuk hal-hal yang dianggap penting oleh pelanggan. Luaran dari penelitian ini adalah publikasi artikel ilmiah dalam jurnal nasional yang tidak terakreditasi. Dari hasil penelitian ini menunjukkan bahwa atribut yang menjadi prioritas pertama untuk dilakukan perbaikan berdasarkan nilai tingkat kepentingan/harapan (expectation) adalah atribut Reliability 4, dan dimensi yang merupakan faktor terpenting dalam pelayanan adalah Dimensi Reliability. Jika berdasarkan nilai tingkat kinerja/persepsi (perception), maka atribut yang menjadi prioritas pertama adalah atribut Tangible 1, dan dimensi dengan kinerja terendah adalah Dimensi Tangibles. Untuk atribut yang menjadi prioritas pertama untuk dilakukan perbaikan berdasarkan skor kepuasan (skor SERVQUAL) adalah atribut Reliability 4. Dari hasil pemetaan dengan matriks IPA berdasarkan atribut, terdapat 12 atribut yang menjadi prioritas utama, yaitu: Tangible 1, Tangible 4, Reliability 1, Reliability 2, Reliability 3, Reliability 4, Responsiveness 2, Assurance 4, Assurance 5, Emphaty 2, Emphaty 3, Emphaty 4. Sedangkan dari hasil pemetaan matriks IPA berdasarkan dimensi, prioritas utama perbaikan bagi pelayanan Fakultas Teknik UEU adalah Dimensi Reliability yaitu kehandalan dalam memenuhi janji kepada mahasiswa/i. Kata Kunci : SERVQUAL, importance-performance analysis, kepuasan pelanggan